Measuring Abnormal Performance: The Event Parameter Approach Using Joint Generalized Least Squares - Malatesta, Paul H. (Journal of Financial and Quantitative Analysis, 1986)
Paul H. Malatesta, Measuring Abnormal Performance: The Event Parameter Approach Using Joint Generalized Least Squares, The Journal of Financial and Quantitative Analysis, Vol. 21, No. 1 (Mar., 1986), pp. 27-38